Computer-Based Technology on Writing Performance: A Systematic Literature Review - Tusino, Tusino; Dewi, Puspa; Lestari, Endah; Onate, Rafael V.; Chen, Yinghuei; Mezentsev, Ivan (Universitas Pendidikan Mandalika, 2024)
This systematic literature review delves into the transformative effects of computer-based technology on writing performance, with a specific focus on studies conducted between 2017 and 2023. The review scrutinizes the impact of a diverse array of technologies, ranging from popular platforms like TikTok, Twitter, and Instagram to specialized tools such as Grammarly, Digital Storytelling, and Kahoot. By synthesizing findings from these studies, the review elucidates the multifaceted ways in which technology influences students' writing proficiency. Key findings underscore the nuanced impacts of these technologies, revealing their significant roles in fostering motivation, enhancing language skills, promoting engagement, and facilitating collaborative learning environments. Notably, Grammarly emerges as a prominent tool widely utilized to address grammatical, spelling, and punctuation errors, thereby aiding in the refinement of writing quality. Meanwhile, platforms like Instagram are recognized for nurturing creativity, Twitter for facilitating personalized learning experiences, and Kahoot for fostering active engagement through interactive quizzes and games. By illuminating the diverse dimensions of technology's transformative role in writing performance, this review offers valuable insights for educators, policymakers, and researchers alike. It underscores the importance of leveraging technology as a strategic tool to enhance students' writing skills and foster a dynamic and enriching learning experience. Moreover, it highlights the need for continued exploration and adaptation of innovative technological solutions to meet the evolving needs of modern education.